An Immersed Boundary Method for Simulation of Moving Object in Fluid Flow - Pham, Van Sang (Old Journal, 2018)
Numerical modelling for the interaction between fluid flow interacting and moving object is a quite complicated problem in computational engineering. Such modelling requires solving simultaneously Navier–Stokes equation for fluid flow and Newton equation for object motion. Due to the motion, computational mesh needs to be re-generated in every time step, making the modelling complicated and time consuming. In this paper, we introduce a numerical method which utilizes immersed boundary to represent motion of solid object under effect of 3-dimension fluid flow. In the current method, we developed a numerical method for enforcing viscous boundary conditions on the immersed boundary. The method was validated and applied to simulate the inertial focusing of solid particle in spiral channel, obtained result well matches with experimental observation indicating the accuracy of the developed method.